Cell Phone Viewing Distance and Age in a Chinese Population. - Min Lan; Rosenfield, Mark; Liu, Longqian (Optometry & Visual Performance, 2018)
Background: A previous study from our laboratory demonstrated that the average viewing distance adopted when viewing a smartphone in American subjects was closer than the reading distance typically found when viewing printed materials. Given the very high prevalence of myopia in China (approaching 90% in some areas), the aim of this investigation was to measure the mean cell phone viewing distance in a Chinese population, and to examine the effect of age on this parameter. Methods: 207 Chinese subjects were instructed to view a text message on their cell phone, and to hold the device as if they were about to read the text. The distance from the phone to the spectacle plane was measured using a rigid tape measure. Results: The mean viewing distance was 33.95cm (SD = 5.90cm, range 19.0 - 51.3cm). A weak but significant positive correlation (r = 0.24, p < 0.0001) was found between age and viewing distance. No significant difference in viewing distance was observed when comparing spectacle (N=84) versus non-spectacle (N = 123) wearers (p = 0.91). Conclusions: These findings confirm the previous results that modern cell phones are held at closer viewing distances than printed materials. Further, the mean viewing distance adopted in a Chinese population was over 2cm closer than that found in American subjects. This increased demand on both ocular accommodation and vergence compared with hardcopy materials could be responsible for symptoms of digital eye strain commonly experienced in many individuals.